The UTAUT Model Explaining Intentions to Use Telemedicine Among Thai People During the COVID-19 Pandemic: A Qualitative Study in Krabi, Thailand - Limna, Pongsakorn; Siripipatthanakul, Supaprawat; Siripipattanakul, Sutithep; Auttawechasakoon, Pichakoon (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose   – This study aims to explain the influence of the unified theory of acceptance and use of technology (UTAUT) model on individuals’ intentions to use telemedicine among people in Krabi, Thailand, during the COVID-19 pandemic. Method – In this study, the qualitative approach was used as a research strategy. In-depth interviews were conducted with six key informants to determine the intention to use telemedicine during the COVID-19 pandemic related to the UTAUT model in Krabi, Thailand.  Thematic analysis and NVivo were employed to analyse the qualitative data. Results – Telemedicine is an essential technology for remote or online consultations between healthcare providers and patients during the COVID-19 pandemic. Moreover, the four key dimensions of the UTAUT model (performance expectancy, effort expectancy, social influence, and facilitating conditions) impact individuals’ intentions to use telemedicine during the COVID-19 pandemic in Krabi, Thailand. Conclusion – Telehealth is an important tool for providing remote healthcare, and its popularity has grown during the COVID-19 pandemic. The UTAUT model adoption is critical as it is related to individuals' intention to use telemedicine. Recommendations – Healthcare providers and directors should consider the UTAUT model adoption in telemedicine technology because it is related to individuals' intention to use telemedicine during the COVID-19 pandemic and beyond. Research Implications – This study added to the existing literature on the UTAUT model (performance expectancy, effort expectancy, social influence, and facilitating conditions) to explain telemedicine and intentions to use telemedicine. Hence, this study's findings may aid academics in broadening their research by incorporating more potential elements. Practical Implications – The study's findings may benefit healthcare providers and directors in developing and implementing a strategy to meet the needs and expectations of individuals or patients using telemedicine during the COVID-19 pandemic and beyond.